ISWI1 complex proteins facilitate developmental genome editing in Paramecium - Singh, Aditi; Häußermann, Lilia; Emmerich, Christiane; Nischwitz, Emily; Seah, Brandon K.B.; Butter, Falk; Nowacki, Mariusz; Swart, Estienne C. (Genome Research, 2025)
One of the most extensive forms of natural genome editing occurs in ciliates, a group of microbial eukaryotes. Ciliate germline and somatic genomes are contained in distinct nuclei within the same cell. During the massive reorganization process of somatic genome development, ciliates eliminate tens of thousands of DNA sequences from a germline genome copy. Recently, we showed that the chromatin remodeler ISWI1 is required for somatic genome development in the ciliate Paramecium tetraurelia. Here, we describe two high similarity paralogous proteins, ICOPa and ICOPb, essential for their genome editing. ICOPa and ICOPb are highly divergent from known proteins; the only domain detected showed distant homology with the WSD (WHIM2 + WHIM3) motif. We show that both ICOPa and ICOPb interact with the chromatin remodeler ISWI1. Upon ICOP knockdown, changes in alternative DNA excision boundaries and nucleosome densities are similar to those observed for ISWI1 knockdown. We thus propose that a complex comprising ISWI1 and either or both ICOPa and ICOPb are needed for Paramecium’s precise genome editing.
10.1101/gr.278402.123